Atypical Presentation of Subacute Sclerosing Panencephalitis in a Child - Monika Hooda; Priyanka Shokeen; Brijesh Kumar; Bhawna Singhal (Wolters Kluwer Medknow Publications, 2024)
Background: Subacute sclerosing panencephalitis (SSPE) is a rare complication of measles, which emerges long after the initial infection. The diagnosis of SSPE can be challenging, especially when initial presentation is atypical. Clinical Description: A 6-year-old boy, apparently healthy previously, presented with a sudden onset of generalized myoclonic jerks with intact cognitive and scholastic skills. Past history revealed that the child had measles infection at 7 months of age. Clinical examination, including memory and intellect assessment, was normal except for the generalized myoclonus. Management and Outcome: Diagnosis of SSPE was confirmed with positive antimeasles antibodies and characteristic pseudoperiodic pattern on electroencephalogram. The child was started on standard treatment as per the existing guidelines. However, the child showed marked deterioration over the next 4 weeks with loss of cognition and intellect, causing hopelessness and grief in the family, leading to their self-withdrawal from further treatment. Conclusion: This case report describes the importance of considering SSPE as a potential diagnosis in patients with myoclonic jerks but intact cognitive and intellectual function. Furthermore, the case portrays the progressive deterioration and profound emotional impact on the family of child with this disease.